2016
DOI: 10.1080/1475939x.2016.1163283
|View full text |Cite
|
Sign up to set email alerts
|

Preparing pre-service teachers to integrate technology into K–12 instruction: evaluation of a technology-infused approach

Abstract: The quality of how technology is addressed in teacher education programmes is conditional for how student teachers apply technology in secondary schools after their graduation. Two technology-infused courses of one teacher education programme were evaluated. In line with studies on the development of pre-service teachers' technological, pedagogical and content knowledge, two important enablers were distinguished: (1) teaching practice to enact what was learned in teacher education institution as well as to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 32 publications
(46 reference statements)
4
59
0
18
Order By: Relevance
“…We found that modeling by college lecturers also influenced the diversity of teaching methods used by pre-service teachers, in accordance with other studies (for example, Admiraal et al, 2017;Tondeur et al, 2012). As teacher educators become more creative in integrating ICT in teaching, so will preservice teachers adopt and implement more innovative teaching methods.…”
Section: Discussionsupporting
confidence: 72%
“…We found that modeling by college lecturers also influenced the diversity of teaching methods used by pre-service teachers, in accordance with other studies (for example, Admiraal et al, 2017;Tondeur et al, 2012). As teacher educators become more creative in integrating ICT in teaching, so will preservice teachers adopt and implement more innovative teaching methods.…”
Section: Discussionsupporting
confidence: 72%
“…In terms of teacher education, producing digitally-literate students has generally meant the prioritisation of technical skills in using digital tools and systems deemed appropriate to educational settings, and identifying how these can be used within particular units of learning (Admiraal et al 2016). This approach assumes that doing this, "equips preservice teachers with a set of basic competencies they can transfer to their future classroom practice" (Admiraal et al 2016, p. 106).…”
Section: Digital Literacy or Digital Competence?mentioning
confidence: 99%
“…Teachers' perceived capacity was measured by five items based on the self-efficacy scale to use technology of Admiraal et al (2017). The items were adapted to fit the purpose of this study.…”
Section: Capacitymentioning
confidence: 99%